2012
DOI: 10.1155/2012/815953
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively Activated Macrophages in Types 1 and 2 Diabetes

Abstract: Macrophages are innate immune cells derived from monocytes, which, in turn, arise from myeloid precursor cells in the bone marrow. Macrophages have many important roles in the innate and adaptive immune response, as well as in tissue homeostasis. Two major populations have been defined: The classically activated macrophages that respond to intracellular pathogens by secreting proinflammatory cytokines and reactive oxygen species and alternatively activated macrophages which are induced during Th2 responses dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 88 publications
(97 reference statements)
1
68
1
Order By: Relevance
“…To date, the conclusions of studies on the expression and function of CYP7A1 in patients with type II DM and in associated animal models have been inconsistent (Shin and Osborne, 2008;Espinoza-Jiménez et al, 2012). The results of this study did not find abnormal CYP7A1 expression in the macrophages of patients with type II DM.…”
Section: Discussioncontrasting
confidence: 60%
“…To date, the conclusions of studies on the expression and function of CYP7A1 in patients with type II DM and in associated animal models have been inconsistent (Shin and Osborne, 2008;Espinoza-Jiménez et al, 2012). The results of this study did not find abnormal CYP7A1 expression in the macrophages of patients with type II DM.…”
Section: Discussioncontrasting
confidence: 60%
“…Recent studies have demonstrated that the imbalance of macrophages plays an important role in autoimmune diseases [29][30][31][32][33]. In SLE, overactive M1 macrophages or macrophages induced by activated lymphocyte-derived DNA (ALD-DNA) contributed to the onset of lupus-like diseases in mice [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…4,11 CD16 + monocyte subsets are expanded in inflammatory and infectious conditions such as in neurological diseases, atherosclerosis, coronary heart disorders, cancer, and aging. 4,[12][13][14][15][16][17][18][19] Both the CD14 + + CD16 + and CD14 + CD16 + + monocyte subsets are expanded in the peripheral blood of HIV-infected subjects, suggesting that infection by HIV of this cellular compartment may contribute to the virus reservoir. [20][21][22] Remarkably, HIV-infected macrophage populations derived from CD16-positive monocytes, in contrast to those derived from CD16-negative monocytes, are better able to transfer the virus to resting CD4 + T cells in vitro.…”
Section: Introductionmentioning
confidence: 99%